Business Model Innovation with a Business Model Canvas Approach at Martabak MM - Nanda Cahya Muhamad; Sunu Puguh Hayu Triono (Indonesian Academy of Social and Religious Research (IASRR), 2023)
CV. MM Satu Tujuan is a company engaged in the food & beverage sector located in Bandung with the main product selling martabak called Martabak MM. Martabak MM has 11 branches spread across the city of Bandung. To improve competitiveness, the company can evaluate its business model. This study aims to determine the current business model and propose a new business model for Martabak MM using the Business Model Canvas approach. This business model allows mapping using nine interconnected blocks. The steps needed to map this business model are first conducting observations and interviews to obtain data, after that, designing a Value Proposition Canvas to find out the benefits that customers expect from the products and services that customers need (fit between value proposition and customer segment). After the Value Proposition Canvas, the next step is to analyze the business environment to find out the internal strengths and weaknesses of Martabak MM and the Opportunities and threats of the external environment that are being faced, and the last step is to design a new business model to be proposed to Martabak MM using the Business Model Canvas.